Obstacles Avoidance in Mobile Robot Using Fuzzy Logic Type II Controller - متوج, فادي; ابراهيم, محمد (Latakia University Journal -Engineering Sciences Series, 2021)
The obstacles while mobile robot navigation varies due to the variance of the environment (indoor or outdoor), and the sort of the obstacle itself (static or dynamic). For these reasons, we consider providing the robot with suitable sensors and installing them properly as a meaningful step, these sensors might be cameras, ultrasonic or and other distance measurement. Many algorithms of artificial intelligence is useful to enhance the navigation of the mobile robot and to help it avoiding any possible obstacle on its path, such as fuzzy logic type I and type II, neural networks and artificial neural fuzzy networks (ANFIS). In this paper, we discussed the obstacles facing mobile robot on its path to the destination, and avoiding it without collisions using fuzzy logic type II controller, results cleared that this controller gives effective solutions to avoid any type of obstacles